2001
DOI: 10.1093/sp/8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Signs and Regimes: Rereading Feminist Work on Welfare States

Abstract: This paper reviews and reconstructs recent feminist work on welfare states and social policy regimes. We argue that the concept of "regime" should be stretched to incorporate the way that signs organize the relations among subjects authorized to operate on the field of power. We focus on feminist debates over the status of "maternalism" in welfare movements and states to put forward our expanded, culturalist conceptualization of gender regimes. Feminist research on welfare states has been an intellectually adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 2 publications
0
37
0
1
Order By: Relevance
“…Moreover, we should investigate why some hailings, using some signs-say, of "mother" or "citizen" or "submissive wife" or "mama grizzly"-resonate with some subjects (people!) more than others (Adams 2005;Adams and Padamsee 2001;Padamsee and Adams 2002; on interpellation, see also Wingrove 1999). These claims are also developed by feminist scholars who combine historical excavation and ethnographic investigation to probe how state regulation and the constitution of subjected agency work "on the ground," for example in Lynne Haney's fine books on "inventing the needy" (Haney 2002) and new therapeutic technologies of punishment (Haney 2010); here, the significance of "desires" as well as interests is underlined.20 We should not give up the insights of culturalism with respect to understanding agency, subject formation, power, culture, gender, empire, and race.…”
Section: Where Does That Leave Us Now In Historical Social Science Anmentioning
confidence: 92%
“…Moreover, we should investigate why some hailings, using some signs-say, of "mother" or "citizen" or "submissive wife" or "mama grizzly"-resonate with some subjects (people!) more than others (Adams 2005;Adams and Padamsee 2001;Padamsee and Adams 2002; on interpellation, see also Wingrove 1999). These claims are also developed by feminist scholars who combine historical excavation and ethnographic investigation to probe how state regulation and the constitution of subjected agency work "on the ground," for example in Lynne Haney's fine books on "inventing the needy" (Haney 2002) and new therapeutic technologies of punishment (Haney 2010); here, the significance of "desires" as well as interests is underlined.20 We should not give up the insights of culturalism with respect to understanding agency, subject formation, power, culture, gender, empire, and race.…”
Section: Where Does That Leave Us Now In Historical Social Science Anmentioning
confidence: 92%
“…A pioneering strand of this literature sought to develop new welfare state typologies in which gender is incorporated as a key source of variation (e.g. Lewis, 1992;Sainsbury, 1996;Adams & Padamsee, 2001). Although some researchers have questioned whether these new typologies were too narrowly focused on mothers and/or female employment (Jensen, 1997;Brush, 2002), this body of work has made a valuable contribution by identifying variation in the ways that welfare state ideology and policies assume and reinforce the traditional gender division of labour within families.…”
Section: The Use Of Comparative Methodsmentioning
confidence: 99%
“…The Three World typology and its relevance for gender outcomes, however, remained controversial (Adams and Padamsee 2001). Lewis (1992) had already showed that gender regimes do not necessarily coincide with Esping-Andersen's welfare regime: the male-breadwinner principle was quite modified in France (classified as a conservative welfare state) and rather strongly implemented in the UK (classified as a liberal welfare state).…”
Section: Fi Already Exists: the Literature On Gender And Welfare Regimesmentioning
confidence: 99%